Kejadian Penyakit Blas Pada Varietas Padi Inpari Sidenuk di Desa Waimital Kecamatan Kairatu, Kabupaten Seram Bagian Barat - Dien Ulate; Handry R.D. Amanupunnyo; Aminuddin Umasangaji; Rhony Einstein Ririhena; Christoffol Leiwakabessy (JURNAL PERTANIAN KEPULAUAN, 2020)
Rice (Oryza sativa. Linn) is a staple food source for most of the population in the region of Asia, including Indonesia. The research aimed to determine the level of Blast disease attack (Pyricularia oryzae/P. oryzae Cav) to Rice var. Inpari Sidenuk in Waimital village, Kairatu sub-district. This study was held from March to August 2018 against 30 rice groves. Observations were conducted to check the symptoms of the Blast disease and the severity of the disease in the field and analyzed descriptively. The results showed that the average severity of high blast disease was 88.67%. Besides, climate factors determine the high level of damage to this disease on the farm, so it is necessary to look for alternative environmentally friendly and sustainable disease control techniques.